Uso do instrumento XP-ENDO FINISHER no índice de sucesso do tratamento endodôntico de dentes posteriores: ensaio clínico randomizado controlado - Oliveira, Ludmila Smith de Jesus (2022)
The XP-endo Finisher was introduced as a supplemental approach to improve sanitization during chemical-mechanical preparation. The aim of this randomized and controlled clinical trial was to evaluate the effect of the complementary use of XP-endo Finisher on postoperative pain and the success rate after endodontic treatment. Ninety-two posterior teeth with pulp necrosis and apical periodontitis greater than 2 mm in diameter were randomized to be instrumented with a single reciprocating file followed or not (control) by further activation with XP-endo Finisher. Postoperative pain was assessed at 24, 48, 72 hours and seven days after endodontic treatment (single session) using a universal pain assessment tool. Treatment success was calculated based on regression of the apical lesion (reduction in the PAI index) and absence of clinical signs after a 6-month follow-up. Data regarding the incidence of postoperative pain and analgesic need were analyzed using the chi-square test. The proportion of healed, healing and non-healed lesions, as well as the success rate, was also evaluated by the chi-square test. The odds-ratio for risk of postoperative pain and success of endodontic treatment was adjusted by logistic regression. There was no loss to follow-up for postoperative pain outcome. Approximately 50% of the participants had some postoperative pain in the first 24 hours after endodontic treatment, with a reduction to less than 20% after 72 hours. Around 25% of the participants required some analgesic medication in the first 24 hours after endodontic treatment, with a reduction to less than 20% after the first 24 hours, 10% after 48 hours and only two patients after 7 days. There was no difference between the interventions. At 6-month follow-up, the loss to follow-up was 19.8%, and the healing rate of lesions in the experimental group was 45.5% and 42.5% for the control group. The percentages of lesions in the healing process were 17.5% and 9.1% for the control and experimental interventions, respectively. None of the independent variables (operator, sex, age, educational level, self-reported health, skin color, fistula, provoked pain, groups of teeth) affected the chances of healing the lesions or the success of the treatment. Regardless of the odds-ratio adjustment, the use of the XP-endo Finisher did not affect the success of endodontic treatment 6 months after the intervention. Both protocols resulted in a similar success rate and healing of periapical lesions. Complementary use of the XP-endo Finisher file had the same incidence or level of postoperative pain, lesion healing, and reported success after endodontic treatment as the control intervention.